New numerical tools to calibrate the Two Curves Method using the CTOA criterion. (January 2019) - Ben Amara, M.; Pluvinage, G.; Capelle, J.; Azari, Z.
Abstract: Based on the Crack-Tip Opening Angle (CTOA) fracture criterion and the finite element method coupled with the node release technique, a New Two-Curve method (TCM) was proposed for the prediction of gas pipelines' crack arrestability. Arrest pressure, crack propagation velocity and length were predicted successfully. A modern high-toughness pipeline made in API 5L X65 pipeline steel with 19 mm wall thickness and a 355 mm external diameter was investigated. The critical CTOA ( CTOAC ) property was measured with a Modified Compact Tension (MCT) specimen at room temperature. A new method for evaluating the CTOAC by combining experimental load–deflection data and finite element analysis was implemented. The results of the CTOAC were compared with the available CTOAC data. The results for the New Two-Curve method were discussed and compared with those obtained by well-established methods such as Battelle-TCM, HLP and HLP-Sumitomo.